Effectiveness of interventions that support penicillin allergy assessment and de-labeling of patients by non-allergy specialists: a systematic review protocol. Issue 2 (25th February 2022) - Powell, Neil; Kohl, Declan; Ahmed, Shadia; Kent, Bridie; Sandoe, Jonathan; Tonkin-Crine, Sarah; Owens, Rhys; Stephens, Jennie; Upton, Mathew
ABSTRACT: Objective: This review will systematically examine and synthesize the evidence evaluating the effectiveness and safety of interventions that enable non-allergy specialist health care workers to assess allergy risk in patients with reported penicillin allergies and subsequently remove erroneous allergy records. Introduction: The potential benefits of removing erroneous penicillin allergy labels (de-labeling) are wide-ranging. Penicillin allergy assessment and de-labeling is an antibiotic stewardship priority. Delivery of such assessment and de-labeling by non-allergy specialists has been reported in several studies, but the effectiveness and safety have not been formally synthesized. This is a necessary step in the upscaling of penicillin allergy assessment services. Inclusion criteria: This review will consider quantitative studies using appropriate designs. The studies will include adults and pediatric patients who have undergone penicillin allergy assessment and de-labeling by non-allergy specialists in any health care setting. Methods: A range of databases will be searched to identify studies published in English, with no date limit applied. Unpublished studies and gray literature will also be searched. Title and abstract screening, and assessment of selected full texts against the inclusion criteria will be conducted by at least two independent reviewers. Identified studies will be assessed for methodological quality using standardized critical appraisal instruments. Data will be extracted and categorized using the EPOC taxonomy, and the effectiveness and safety of the intervention will be determined. Where possible, data will be pooled to facilitate meta-analysis. Data from heterogeneous studies will be reported narratively. The GRADE approach for grading the certainty of evidence will be followed. Systematic review registration number: PROSPERO CRD42020219044